2023
DOI: 10.1227/neu.0000000000002621
|View full text |Cite
|
Sign up to set email alerts
|

Letter: The Impact of Extent of Ablation on Survival of Patients With Newly Diagnosed Glioblastoma Treated With Laser Interstitial Thermal Therapy: A Large Single-Institutional Cohort

Abstract: To the Editor:We read with great enthusiasm the article regarding the impact of the extent of ablation using laser interstitial thermal therapy (LITT) in survival of patients with newly diagnosed glioblastoma published by Kaisman-Elbaz et al. 1 LITT provides a valuable alternative of treatment for patients with few surgical options, such as diagnosis of highly eloquent and/or deep-seated glioblastomas (GBM), and for patients who have a high frailty index. [2][3][4] To date, the literature has highlighted incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…We agree with Awan et al 1 regarding the potential of excess ablation contribution to glioblastoma patients' overall survival and progression-free survival, possibly similar to supramaximal resection accumulating data. In our study, no benefit regarding those oncological parameters was demonstrated.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…We agree with Awan et al 1 regarding the potential of excess ablation contribution to glioblastoma patients' overall survival and progression-free survival, possibly similar to supramaximal resection accumulating data. In our study, no benefit regarding those oncological parameters was demonstrated.…”
supporting
confidence: 92%
“…In their letter, Awan et al 1 referred to the high excess ablation rate detected in 84% of our patient cohort 2 that was not found to cause a new postprocedural neurological deficit. They describe thoroughly the importance of protecting critical brain structures such as the corticospinal tract during laser interstitial thermal therapy and evaluating the distance of those structures from the treated lesion before the procedure.…”
mentioning
confidence: 77%
See 2 more Smart Citations